Pengabdian Mandiri Kemitraan Masyarakat Penguatan Literasi Keuangan untuk Mendukung Keberlanjutan Usaha Tenank Cafe Medan - Riswanto Riswanto; Khairul Khairul; Cut Nizma; Diena Fadhilah; Jasa Ginting (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in national economic growth, particularly in creating employment opportunities and improving community welfare. However, many MSME actors still face challenges in financial management due to limited financial literacy and inadequate understanding of simple accounting practices. Tenank Cafe Medan is one of the culinary businesses with strong development potential, yet it continues to experience difficulties in transaction recording, cash flow management, and preparing simple financial reports, which may affect business sustainability and operational effectiveness. This Community Partnership Independent Service Program (PMKM) aims to improve the financial literacy of business partners in supporting sustainable business development. The implementation methods included observation, socialization, training, direct practice, and mentoring activities focused on business financial management and transaction recording. The results of the program indicate an increase in the partner’s understanding of financial management, transaction recording, and the preparation of simple profit and loss reports. In addition, the partner has started to separate business finances from personal finances. Therefore, this activity provides a positive contribution toward strengthening business management practices and supporting the sustainability and long-term development of Tenank Cafe Medan.